Strange Bedfellows: Subjectivity, Romance, and Hidden Object Video Games. (November 2014) - Chess, Shira
At first blush, the romance might seem antithetical to gaming. The masculine hegemony of the video game industry creates specific genre expectations about video games. Just as "extending play" is about opening itself to new kinds of ways that people play, it also encompasses extending to new audiences. At the same time, there is always a risk of ghettoizing new audiences—reinforcing stereotypes that keep gamers marginalized. This essay analyzes one such extension: the complex relationship between the romance novel and the video game. Modleski illustrates how romance in books, television, and film are often dismissed as frivolous, but also demonstrate how audiences use romantic texts for a wide variety of purposes. Although universal, romance is an experience that can be understood as both general and specific as well as generic and subjective. The video game romance, while not a perfected genre, often struggles with these larger questions about identity and subjectivity. This article explores the tension between subjectivity and interactivity, as it relates to romance and gaming, specifically in the hidden object gaming genre. Analysis focuses on three romance-themed game texts: Harlequin: Hidden Object of Desire, Ravenhearst, and Love and Death: Bitten . With each of these games, I examine the different modes of interactive romance and demonstrate how subjectivity functions within the gameplay, complicating traditional notions of identity and subjectivity within the romance. Additionally, I illustrate how the games ignore the potential of player agency in favor of formulaic structures and subjectivities.